Learning from the failures of drug discovery in B-cell non-Hodgkin lymphomas and perspectives for the future: chronic lymphocytic leukemia and diffuse large B-cell lymphoma as two ends of a spectrum in drug development. (3rd July 2017) - Kubuschok, Boris; Trepel, Martin
ABSTRACT: Introduction : Despite substantial recent advances, there is still an unmet need for better therapies in B-cell non Hodgkin lymphomas (B-NHL), especially in relapsed or refractory disease. Many novel targeted drugs have been developed based on a better molecular understanding of B-NHL. Areas covered : This article focuses on chronic lymphocytic leukemia (CLL) as a representative for indolent lymphomas and paradigmatic for the tremendous progress in treating B-NHL on the one hand and diffuse large B-cell lymphoma (DLBCL) as a representative for aggressive lymphomas and paradigmatic for many unsolved problems in lymphoma treatment or the other hand. We highlight salient points in current therapies targeting genetic, epigenetic, immunological and microenvironmental alterations. Possible reasons for drug failure in clinical trials like tumor heterogeneity, clonal evolution and drug resistance mechanisms are discussed. Based thereon, some perspectives for further drug discovery are given. Expert opinion : In view of the pathogenetic complexity of lymphomas, therapies targeting exclusively a single alteration may fail because resistance mechanisms are present either initially or evolve during treatment. Therefore, future therapies in B-NHL may have to target the greatest possible number of genetic, immunological or epigenetic alterations still allowing tolerability and to monitor these alterations during therapy.